Planteamiento de alternativa para la compra de boletos virtuales que permita al usuario el acceso a los buses utilizando la ayuda de los Lectores de Código QR en el Terminal de Babahoyo para evitar la propagación del covid 19 - Vargas Figueroa, Andrew Aldhair (2020)
The present case study on the "ALTERNATIVE APPROACH TO PURCHASE VIRTUAL TICKETS THAT ALLOWS THE USER TO ACCESS THE BUSES USING THE HELP OF THE QR CODE READERS AT THE BABAHOYO TERMINAL TO AVOID THE SPREAD OF COVID 19". The main objective is to show an immediate solution to avoid the crowding of people when obtaining their ticket in order to reduce the spread of the virus in these times of pandemic. The implementation of this alternative provides precise information on the departure times of the buses, prices and routes of the cooperatives that go to said destination. It is intended to educate passengers by introducing this type of technological tools as mobile applications that streamline manual processes and automate them. A field work was carried out that helped us obtain primary and secondary information to verify if the proposed proposal provided an optimal solution to travelers. The case study is composed of introduction, development, conclusions based on the research done previously. The surveys obtained from visitors and people who frequent the Babahoyo land terminal were carried out and analyzed and it was determined that the proposal put forward in it would provide a very optimal solution not only to prevent the spread of the Covid19 virus, but also to help streamline the purchase processes at the ticket offices and help to reserve bus tickets, receive a ticket with a QR code that you can use without having to be printed.